Magnetic resonance assessment of gastrointestinal tract inflammation in Crohn’s disease using the simplified MaRIA score In a Colombian center: MAGNETIC study - Parra Izquierdo, Viviana (2025)
Introduction: Magnetic Resonance Enterography (MRE) is a valuable imaging modality for the evaluation and follow-up of patients with inflammatory bowel disease (IBD), particularly Crohn’s disease (CD). This study describes MRE findings in patients with suspected or confirmed CD at a national reference center for IBD in Colombia. Materials and methods: A descriptive observational study was conducted in patients evaluated with MRE at a specialized IBD center. Results: Of the 20 patients evaluated, 18 (90%) underwent MRE due to clinical or endoscopic suspicion of Crohn’s disease, while 2 patients (10%) had a previously confirmed diagnosis and were assessed for follow-up evaluation. Overall, 40% of the cohort showed findings compatible with acute inflammatory activity. Overall, 40% of the cohort showed findings compatible with acute inflammatory activity. Intestinal involvement was most frequent in the terminal ileum (40%), followed by the sigmoid colon (15%), and the descending, transverse, and cecum colon (10% each). The average ileal segment length was 37 mm, with mean parietal thickening of 5.7 mm. Mesenteric fat signal alteration was observed in 55% of patients, mesenteric lymphadenopathy in 35%, and vascular changes in 10%. Chronic fibrostenotic changes were found in 15%, and 20% showed subocclusive-type obstructions. Findings not related to IBD were noted in 35% of cases. Based on the simplified Magnetic Resonance Index of Activity (MaRIA) score, 50% had a score of 0-1, 5% scored 2, 40% scored 3, and 5% scored 5. Conclusions: The MAGNETIC study confirms MRE’s role in identifying active inflammation, chronic sequelae, and complications in Crohn’s disease. It supports the use of the MaRIA score for objective disease assessment, enhancing clinical decision-making in specialized IBD centers.